A Multi-Centric Study Assessing Safety and Efficacy of Everolimus in Adult Chinese Patients With Tuberous Sclerosis Complex Associated Renal Angiomyolipomas - Wang, Wenda; Guo, Gang; Shi, Guohai; Wei, Xin; Hu, Zhiquan; Li, Hanzhong; Zhang, Xu; Ye, Dingwei; Zhang, Yushi (Frontiers in Oncology, 2022)
Background: Everolimus has been approved in China for adult patients with TSL-AML not requiring immediate surgery and has been previously shown to be an effective treatment option for TSL-AML in the Chinese population. Methods: This is an open label, single arm, multi-center Phase IV post-approval commitment study to further assess the safety and efficacy of everolimus in patients with TSC-AML who do not require immediate surgical intervention. The primary outcome was to evaluate the safety of everolimus while the secondary outcome was to evaluate AML response. Results: Treatment with everolimus was associated with a clinically meaningful best overall AML response rate of 70% (95% CI: 53.5, 83.4). Of the 38 evaluable patients, 37 (97%) patients experienced a reduction in the sum of volumes of target angiomyolipoma lesions relative to baseline. At Week 12 (n=38), the median percentage reduction in sum of target AML volume was −56.60%, which further increased to -59.96% at Week 24 (n=38), to reach −64.41% at Week 48 (n=22). Throughout the study, renal function remained relatively stable. Patients with TSC associated lymphangiomyomatosis (LAM) (N=13) demonstrated a lower than expected rate of decline in PFTs. Everolimus was generally well tolerated with no significant safety findings in Chinese patients. Most of the adverse events were of grade 1-2, and manageable with appropriate dose adjustments and supportive therapies. There were no treatment discontinuation due to AE and no treatment death was reported. Conclusions: Based on the efficacy and safety data presented in this study, the overall clinical benefit/risk assessment further supports the use of everolimus as a viable treatment option for Chinese patients with TSC-AML.